The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/cssc.201700321
|View full text |Cite|
|
Sign up to set email alerts
|

Expeditious and Solvent‐Free Nickel‐Catalyzed C−H Arylation of Arenes and Indoles

Abstract: An efficient solvent-free nickel-catalyzed method for C-H bond arylation of arenes and indoles has been developed, which proceeds expeditiously through chelation assistance. The reaction is highly selective for mono-arylation and tolerates sensitive and structurally diverse functionalities, such as halides, ethers, amines, indole, pyrrole and carbazole. This reaction represents the first example of a nickel-catalyzed C-H arylation by monochelate assistance and symbolizes a rare precedent in solvent-free C-H ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 115 publications
0
22
0
Order By: Relevance
“…The isolation of a tri-coordinated T-shaped Ni complex with weak (an)agostic Ni … (H-C) interaction invokes C-H bond coordination to Ni(II), forming a sigma-complex as a key step of the process with base neutralising the proton outside of the coordination sphere. Evidence for an inner-sphere attack of coordinated base was provided by Punji et al, who proposed the anion exchange of chloride or acetate by bis(trimethylsilyl)amide as a step precluding N-directed C-H bond activation under solvent-free conditions [35] (Scheme 2). In keeping with this, Musaev et al suggested a cesium/carboxylate cluster as the active basic principle based on computational studies [36].…”
Section: Introductionmentioning
confidence: 99%
“…The isolation of a tri-coordinated T-shaped Ni complex with weak (an)agostic Ni … (H-C) interaction invokes C-H bond coordination to Ni(II), forming a sigma-complex as a key step of the process with base neutralising the proton outside of the coordination sphere. Evidence for an inner-sphere attack of coordinated base was provided by Punji et al, who proposed the anion exchange of chloride or acetate by bis(trimethylsilyl)amide as a step precluding N-directed C-H bond activation under solvent-free conditions [35] (Scheme 2). In keeping with this, Musaev et al suggested a cesium/carboxylate cluster as the active basic principle based on computational studies [36].…”
Section: Introductionmentioning
confidence: 99%
“…The nickel being one of the abundant transition metals, has been employed for the C−H arylation of many activated heteroarenes and arenes bearing bidentate directing groups . Recently, Punji and co‐workers demonstrated the C(2)−H arylation of indoles via a monodentate chelate assistance employing a well‐defined nickel catalyst 1 (Scheme ) . Generally, aryl bromides and iodides worked as suitable coupling partners, whereas aryl chlorides were inefficient.…”
Section: Arylation Reactionsmentioning
confidence: 99%
“…[18] Recently, Punji and co-workers demonstrated the C(2)À H arylation of indoles via a monodentate chelate assistance employing a well-defined nickel catalyst 1(Scheme 5). [19] Generally, aryl bromides and iodides worked as suitable coupling partners, whereas aryl chlorides were inefficient. The reaction tolerated diverse functionalities including halo, ether, amine, pyrazolyl and carbazolyl groups.…”
Section: Ni-catalyzed Reactionsmentioning
confidence: 99%
“…Thus, a generalized protocol for the synthesis of secondary amines by using a commercially available ligand with inexpensive cobalt salt under mild hydrogen source is highly desirable. To address these limitations associated with the existing amination/reductive amination protocols, and within our interest on base-metal catalysis, [20] herein, we report a user-friendly (Xantphos)CoCl 2 catalyst system for the selective reductive amination of nitriles to symmetrical and unsymmetrical secondary amines under mild conditions (Scheme 2B). Thus, the cobalt catalyst selectively reduces the aromatic nitriles to symmetrical secondary amines using ammonia-borane (H 3 NÀ BH 3 ) as a hydrogen source, whereas the use of external amines and dimethylamine borane (Me 2 NHÀ BH 3 ) afforded unsymmetrical secondary and tertiary amines.…”
Section: Abstract: Cobalt; Hydrogenation; Nitriles; Reductive Aminatimentioning
confidence: 99%